A New Future for the Ancient Perennial Mediterranean Vegetable ‘Akkoub (Gundelia spp. and Asteraceae) - David Van Tassel; Aubrey Streit Krug; Yusra Othman; Tala Khouri; Fouad Muaddi; Eyad Taamallah; Ishraq Awashra; Omar Tesdell (Ethnobiology Letters, 2025)
Gundelia has been cooked as a wild edible plant from pastures and open areas in many countries bordering the Mediterranean Sea. The foliage of this hardy, prickly, perennial genus resembles the artichoke (Cynara cardunculus) and has similar culinary uses. However, the heads are quite distinct and produce edible seeds that may once have been harvested as a source of vegetable oil. Though avoided by grazing sheep and goats, the dried foliage is palatable and nutritious when chopped and mixed in animal rations. Independently, several small producers in Palestine have begun sowing and raising Gundelia, known as ‘akkoub, as a crop because of its economic and cultural value, and because of increasingly constrained access to wild stands. An international collaboration could develop improved genetic varieties and agronomic practices to revive its use for oil seeds and to accelerate the domestication of this valuable, hardy plant.